A CLINICAL STUDY TO EVALUATE THE EFFECT OF SPHATIKAYUKTHA RASA SINDOORA WITH LODHRA KASHAYA IN DYSFUNCTIONAL UTERINE BLEEDING (International Journal of Ayurveda and Pharma Research, 2021)
Dysfunctional Uterine Bleeding is defined as a state of abnormal uterine bleeding without any clinically detectable organic, systemic and iatrogenic cause. The prevalence varies widely but an incidence of 10% amongst new patients attending the outpatient seems logical. Along with increased susceptibility to iron deficiency, heavy menstrual bleeding can negatively impact physical, emotional and social quality of life and reduce work capacity of females. Objective: A clinical study was conducted to evaluate the effect of Sphatikayuktha Rasa Sindoora with Lodhra Kashaya in Dysfunctional Uterine Bleeding. Design: This pre-post interventional study was conducted among 20 females in the age group 20-45 years who had the symptoms of Dysfunctional Uterine Bleeding for the past 3 cycles. Drug administration started on the 3rd day of menstruation and was continued till bleeding stopped or upto a maximum of 7 days for 3 consecutive cycles. Follow up was done in the next cycle. The condition of the patient after drug administration in the first, second and third months were separately compared with the condition of the patient before treatment. Outcome measures: Outcome variables were change in the amount, duration and frequency of bleeding. Results and Discussion: Results were analysed statistically using Wilcoxon signed rank test and Paired t-test. The treatment was effective in reducing the amount of bleeding during treatment period and the follow up period. It was effective in reducing the duration of bleeding during the treatment period as compared to the follow up period and in controlling the cycle interval during the treatment period.